2005
DOI: 10.1007/s00248-004-0232-2
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Food Webs in Boreal Humic Lakes and Reservoirs: Ciliates as a Major Factor Related to the Dynamics of the Most Active Bacteria

Abstract: In order to assess the factors that determine the dynamics of bacteria with high nucleic acid content in aquatic systems, we (i) conducted 24-h in situ dialysis experiments, involving different fractions of plankton and unfiltered water and (ii) examined empirical relationships between bacteria and both abiotic factors and protists, in boreal humic freshwaters (reservoir and lakes) in the James Bay region (Québec, Canada). Bacteria were subdivided into two subgroups on the basis of their nucleic acid content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 47 publications
3
34
0
Order By: Relevance
“…LNA cell abundance did not increase with increasing chl a or bacterial activity, as previously observed in natural samples (Morán et al 2002b, Tadonléké et al 2005 and in dilution-growth experiments (Gasol et al 1999, Vaqué et al 2001, altogether supporting their identification with inactive or dead cells, as proposed by some authors (Li et al 1995, Jellett et al 1996, Gasol et al 1999. However, the finding that overall LNA bacterial abundance was more variable than that of HNA cells (76 vs. 62% CV; see also Table 1), if not an indirect result of factors acting on HNA bacteria, could suggest that this group of cells was able to show some response to environmental forcing (Seymour et al 2005, Sherr et al 2006).…”
Section: Nucleic Acid Content and Activity Of Natural Bacterial Commusupporting
confidence: 78%
See 1 more Smart Citation
“…LNA cell abundance did not increase with increasing chl a or bacterial activity, as previously observed in natural samples (Morán et al 2002b, Tadonléké et al 2005 and in dilution-growth experiments (Gasol et al 1999, Vaqué et al 2001, altogether supporting their identification with inactive or dead cells, as proposed by some authors (Li et al 1995, Jellett et al 1996, Gasol et al 1999. However, the finding that overall LNA bacterial abundance was more variable than that of HNA cells (76 vs. 62% CV; see also Table 1), if not an indirect result of factors acting on HNA bacteria, could suggest that this group of cells was able to show some response to environmental forcing (Seymour et al 2005, Sherr et al 2006).…”
Section: Nucleic Acid Content and Activity Of Natural Bacterial Commusupporting
confidence: 78%
“…5). In a recent paper, Tadonléké et al (2005) concluded that grazing by ciliates was a major factor responsible for lack of response of HNA abundance to chl a in a series of lakes. Although mortality by protistan grazers or viral infection was not assessed during the present study, the lower biomass of HNA cells in the East zone could be indicative of a preferential loss of the most active and larger cells within this group.…”
Section: Cell Size Versus Nucleic Acid Contentmentioning
confidence: 99%
“…The physiological state of bacterial cells has also been suggested as a key factor in grazing selectivity (Del Giorgio and Gasol, 2008), and preferential grazing of the more active cells within a community by protist grazers has been repeatedly observed (Del Giorgio et al, 1996;Pernthaler et al, 1997;Simek et al, 1997;Tadonléké et al, 2005;Sintes and Del Giorgio, 2014). This is probably related to the general positive relation between cell size and activity in marine bacteria (Gasol et al, 1995;Hahn and Höfle, 2001;Matz and Jürgens, 2001;Matz et al, 2002;Corno and Jürgens, 2006), suggesting that larger bacterioplankton cells are also usually the most active ones.…”
Section: Introductionmentioning
confidence: 95%
“…It has been shown that heterotrophic nanoflagellates and other planktonic predators seem to prefer grazing on and selectively cropping the largersized and more active fraction of bacterioplankton (Corzo et al 2005;Nishimura et al 2005). Tadonleke and co-workers reported that Cyclidium glaucoma selectively grazed on HNA communities rather than on LNA (Tadonléké et al 2005). Nishimura and colleagues also found that the grazing mortality of HNA bacteria was 2.8-fold higher than that of LNA bacteria in Lake Biwa (Nishimura et al 2005).…”
Section: Geographic Patterns In Abundance Of Lna and Hna Subgroupsmentioning
confidence: 99%